PERAN PENDIDIK DALAM MENANAMKAN NILAI-NILAI PERSATUAN DAN KESATUAN BANGSA TERHADAP PESERTA DIDIK - Ahmad Arif Fadilah; Fawazzul Fida; Firda Roudhotuz Zahra (Sindoro: Cendikia Pendidikan, 2024)
The role of teachers in instilling the values of national unity and unity in students is very important. Instilling a sense of unity and oneness in students will foster a sense of love for their homeland, the Indonesian nation and also sensitivity towards the environment in schools, families and society eith character education in instilling the value of unity. There will be a formation of sensitivity towards the surrounding environment, for example: mutual cooperation, people who need help, they are sensitive and there is a sense of help. This research uses a literature study method with a descriptive approach. The purpose of this research is to find out and provide a strategy or tips for instilling or implementing the values of national unity and unity in students